2018
DOI: 10.1177/1177271918757480
|View full text |Cite
|
Sign up to set email alerts
|

Nkx2-3—A Slippery Slope From Development Through Inflammation Toward Hematopoietic Malignancies

Abstract: The development of peripheral lymphoid tissues from the mesoderm is the result of a complex convergence combining lymphohematopoietic differentiation with the local specification of nonhematopoietic mesenchymal components. Although the various transcriptional regulators with fate-determining effects in diversifying the mobile leukocyte subsets have been thoroughly studied and identified, the tissue-specific determinants promoting the regional differentiation of resident mesenchyme are less understood. Of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…Nirenberg-Kim (NK) 2 homeobox 3 (Nkx2-3) is a homeodomain transcription factor, which is essential for the normal development of the spleen, Peyer’s patches and small intestine [ 14 , 15 , 16 , 17 ]. Along with its role in the development of intestinal lymphoid tissues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nirenberg-Kim (NK) 2 homeobox 3 (Nkx2-3) is a homeodomain transcription factor, which is essential for the normal development of the spleen, Peyer’s patches and small intestine [ 14 , 15 , 16 , 17 ]. Along with its role in the development of intestinal lymphoid tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Along with its role in the development of intestinal lymphoid tissues. Nkx2-3 is crucial for the expression and regulation of the mucosal addressin cell adhesion molecule-1 (MADCAM-1) on the spleen sinus lining cells and on high endothelial venules of the mesenteric lymph nodes and Peyer’s patches [ 17 , 18 , 19 , 20 ]. Nkx2-3 has an important role in spleen organization and function, since it controls the correct micro-environment for B cell maturation and T-cell-dependent (TD) immune reaction [ 14 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…NKX2-3 may also be classi ed as biomarker to predict the effects of primary advanced colorectal cancer patients who will undergo FOLFOX4 [66]. NKX2-3 has been studied not only in solid malignancies, but also in hematopoietic malignancies [67]. Therefore, it is very valuable to further study NKX2-3 in both solid malignancies and hematopoietic malignancies In our study, the expression of autophagy-related gene NKX2-3 was signi cantly up-regulated in prostate cancer tissues compared to the non-tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…NKX2-3 is a homeobox gene that is key for the development of the spleen and the visceral mesoderm, which develops several essential cell types of the gastrointestinal tract including endothelial cells, immune cells, and -notably -smooth muscle cells. Knockout mouse 30 studies have shown that loss of this gene affects spleen architecture, and lymphocyte maturation and homing (35)(36)(37)(38)(39). These findings make a compelling case that lncRNA regulation of NKX2-3 in both the colon and spleen influences ulcerative colitis susceptibility.…”
Section: Co-expression Network Identify Highly Connected Lncrna Genementioning
confidence: 99%